Money Demand Policy Model in Muslim Countries - Larasati Agustina, Ingrid (International Journal of Psychosocial Rehabilitation, 2020)
In the theory of demand for money for Islamic monetary, Umer Chapra uses the Keynesian model as a foothold. From here finally the profit-sharing rate in lieu of interest becomes significant in the model. The question is which one is appropriate as a foothold, classic or Keynes. Which assumptions are actually in accordance with the characteristics of the Islamic financial system which are said to be interest-free, investment to the productive, consumption that is not excessive, with the obligation of zakat, infaq and shodaqoh? The formulation of the problem in this study is how the theory of money demand in Islamic economics and how to model the demand for money in Muslim countries. The method used in this research is a qualitative method using literature studies. The results of this study are that the demand for money in an Islamic country is determined by income, in this case transactions motive and precautionary motive dominates the reason of the Muslim population. Demand for money in the narrow and broad sense is not influenced by the interest rate so the implication is that the preferences of Muslims differ from the Keynesian model, so speculation motives are not found in Islamic countries and the complete elimination of interest rates in Islamic countries will not cause serious problems in relation to the effectiveness of monetary policy in these countries.